# Electronic Properties of Materials/Quantum Mechanics for Engineers/Perturbation Methods

This is the ninth chapter of the first section of the book Electronic Properties of Materials.

**INCOMPLETE**

Most operators (Hamiltonians) are not simple. Fortunately, with a bit of effort, we can sometimes rewrite the operator (${\displaystyle {\hat {H}}}$) as ${\displaystyle {\hat {H}}={\hat {H}}_{o}+\lambda H'}$, where ${\displaystyle {\hat {H}}}$ is a Hamiltonian for which we know the solution.

${\displaystyle {\hat {H}}_{o}\ \psi _{\eta }^{(o)}=E_{\eta }^{(o)}\ \psi _{\eta }^{(o)}}$

Here, ${\displaystyle \psi _{\eta }^{(o)}}$ are non degeneratory orthogonal eigenfunctions, and ${\displaystyle H'}$ is a small perturbation to the ${\displaystyle H_{o}}$. Additionally, ${\displaystyle \lambda }$ is a real arbitrary parameter, and when ${\displaystyle \lambda =0}$, we have:

${\displaystyle {\begin{array}{lcl}H=H_{o}&\ \ when\ \lambda =1\\H=H_{o}+H'&\quad \end{array}}}$

The problem we want to solve is: ${\displaystyle H\psi _{\eta }=E_{\eta }\psi _{\eta }}$

The perturbation is small and in the limit ${\displaystyle \lambda }$ goes to zero.

${\displaystyle E_{\eta }=E_{\eta }^{(o)}+\psi _{\eta }=\psi _{\eta }^{(o)}}$

We will assume that ${\displaystyle E_{\eta }}$ and ${\displaystyle \psi _{\eta }}$ can be written as powers of ${\displaystyle \lambda }$.

{\displaystyle {\begin{aligned}E_{\eta }&=\sum _{j=0}^{\infty }\lambda ^{j}E_{\eta }^{(j)}=E_{\eta }^{(o)}+\lambda E_{\eta }^{(1)}+\lambda ^{2}E_{\eta }^{(2)}+\cdots +\lambda ^{n}E_{\eta }^{(n)}\\\psi _{\eta }&=\sum _{j=0}^{\infty }\lambda ^{k}\psi _{\eta }^{(j)}\end{aligned}}}

Substituting:

${\displaystyle \left(H_{o}+\lambda H'\right)\left(\psi _{\eta }^{(o)}+\lambda \psi _{\eta }^{(1)}+\lambda ^{2}\psi _{\eta }^{(o)}+\cdots +\lambda ^{n}\psi _{\eta }^{(n)}\right)=\left(E_{\eta }^{(o)}+\lambda E_{\eta }^{(1)}+\lambda ^{2}E_{\eta }^{(o)}+\cdots +\lambda ^{n}E_{\eta }^{(n)}\right)\left(\psi _{\eta }^{(o)}+\lambda \psi _{\eta }^{(1)}+\lambda ^{2}\psi _{\eta }^{(o)}+\cdots +\lambda ^{n}\psi _{\eta }^{(n)}\right)}$

Multiply through & collect common properties to form equations for each power of ${\displaystyle \lambda }$:

{\displaystyle {\begin{aligned}\lambda ^{o}:&\quad H_{o}\psi _{n}^{(o)}=E_{n}^{(o)}\psi _{n}^{(o)}\\\lambda ^{1}:&\quad H_{o}\psi _{n}^{(1)}+H'\psi ^{(o)}=E_{n}^{(o)}\psi _{n}^{(1)}+E_{n}^{(1)}\psi _{n}^{(o)}\\\lambda ^{2}:&\quad H_{o}\psi _{n}^{(2)}+H'\psi ^{(1)}=E_{n}^{(0)}\psi _{n}^{(2)}+E_{n}^{(1)}\psi _{n}^{(1)}+E_{n}^{(2)}\psi _{n}^{(o)}\end{aligned}}}

The powers of ${\displaystyle \lambda ^{o}}$ are just our unperturbed ${\displaystyle H_{o}}$. We will begin by looking at powers of ${\displaystyle \lambda ^{1}}$.

Rearrange:

${\displaystyle (H_{o}-E_{n}^{(o)})\psi _{n}^{(1)}+(H'-E_{n}^{(1)})\psi _{n}^{(o)}=0}$

multiply left by ${\displaystyle \psi _{n}^{*(o)}}$ and integrate

${\displaystyle \int \psi _{n}^{*(o)}(H_{o}-E_{n}^{(o)})\psi _{n}^{(1)}+\int \psi _{n}^{*(o)}(H'-E_{n}^{(1)})\psi _{n}^{(o)}=0}$

Begin with left term. These operators are Hermitian. They have special properties, namely that they obey the postulates of quantum mechanics, including a few revations that are useful for proofs. One such property is:

${\displaystyle \int \Psi ^{*}H\Phi =\left(\int \Phi ^{*}H\Psi \right)^{*}}$

Which we will use here:

{\displaystyle {\begin{aligned}\int \psi _{n}^{(o)^{*}}H_{o}\psi _{n}^{(1)}=&\left(\int \psi _{n}^{(1)^{*}}H\psi _{n}^{(o)}\right)^{*}\\=&\left(\int \psi _{n}^{(1)^{*}}E_{n}^{(o)}\psi _{n}^{(o)}\right)^{*}\\=&E_{n}{(o)}\left(\int \psi _{n}^{(1)^{*}}\psi _{n}^{(o)}\right)^{*}\\=&E_{n}^{(o)}\int \psi _{n}^{(o)^{*}}\psi _{n}^{(1)}\end{aligned}}}

Thus, our entire term equals zero. As a result:

${\displaystyle \int \psi _{n}^{(o)}H'\psi _{n}^{(o)}=E_{n}^{(1)}\int \psi _{n}^{(o)^{*}}\psi _{n}^{(o)}=E_{n}^{(1)}}$

Therefore, the first order correction to the eigenvalue is:

${\displaystyle E_{n}^{(1)}=\int \psi _{n}^{(o)^{*}}H'\psi _{n}^{(o)}}$

Following the same steps we can find the higher order perturbations:

{\displaystyle {\begin{aligned}E_{n}^{(2)}&=\int \psi _{n}^{(o)^{*}}\left(H'-E_{n}^{(1)}\right)\psi _{n}^{(1)}\\E_{n}^{(3)}&=\int \psi _{n}^{(1)^{*}}\left(H'-E_{n}^{(1)}\right)\psi _{n}^{(1)}-2E_{n}^{(2)}\int \psi _{n}^{(o)^{*}}\psi _{n}^{(1)}\end{aligned}}}

Most simple theories do not require these higher order corrections, but how do we get the wavefunctions in the first place? Lets assume that ${\textstyle \psi _{n}^{(1)}=\sum _{k}{a_{nk}}^{(1)}{\psi _{k}}^{(o)}}$ where ${\displaystyle a_{nk}}$ coefficient is the projection of ${\textstyle \psi _{n}^{(1)}}$ onto ${\textstyle \psi _{k}^{(o)}}$. Returning to our original ${\displaystyle \lambda '}$ term, gather:

${\displaystyle H_{o}\psi _{n}^{(1)}+H'\psi _{n}^{(o)}=E_{n}^{(o)}\psi _{n}^{(1)}+E_{n}^{(1)}\psi _{n}^{(o)}}$

Rearranging and substituting gives us:

${\displaystyle 0=\left(H_{o}-E_{n}^{(o)}\right)\sum a_{n}^{(1)}\psi _{k}^{(o)}+\left(H'-E_{n}^{(1)}\right)\psi _{n}^{(o)}}$

Multiplying the right side by ${\displaystyle \psi _{\ell }^{(o)^{*}}}$and integrating gets us:

{\displaystyle {\begin{aligned}0&=\int \psi _{\ell }^{(o)^{*}}E_{n}^{(o)}\sum a_{nk}^{(1)}\psi _{k}^{(o)}-E_{n}^{(o)}\int \psi _{\ell }^{(o)^{*}}\sum _{k}a_{nk}^{(1)}\psi _{k}^{(o)}+\int \psi _{\ell }^{(o)^{*}}H'\psi _{n}^{(o)}-E_{n}^{(1)}\int \psi _{\ell }^{(o)^{*}}\psi _{n}^{(o)}\\&=E_{\ell }^{(o)}a_{n\ell }^{(1)}-E_{n}^{(o)}a_{n\ell }^{(1)}+\int \psi _{\ell }^{(o)^{*}}H'\psi _{n}^{(o)}-E_{n}^{(1)}\delta _{n\ell }\end{aligned}}}

When ${\textstyle n=\ell }$, we loose all ${\textstyle a_{n\ell }^{(1)}}$ terms, giving us: ${\displaystyle E_{n}^{(1)}=\int \psi _{\ell }^{(o)^{*}}H'\psi _{n}^{(o)}}$

However, when ${\textstyle n\neq \ell }$ we get:

{\displaystyle {\begin{aligned}0&=\left(E_{\ell }^{(o)}-E_{n}^{(1)}\right)a_{n\ell }^{(1)}+\int \psi _{\ell }^{(o)^{*}}H'\psi _{n}^{(o)}\\a_{n\ell }&={-\int \psi _{\ell }^{(o)^{*}}H'\psi _{n}^{(o)} \over E_{\ell }^{(o)}-E_{n}^{(o)}}\end{aligned}}}

Since ${\displaystyle a_{nn}^{(1)}}$ does not seem to be determined from these equations, there is an uncomfortable degree of arbitrariness in selecting ${\displaystyle a_{nn}^{(1)}}$. Require normalization:

{\displaystyle {\begin{aligned}1&=\int \Psi ^{*}\psi \\1+0\left(\lambda ^{j+1}\right)&=\int \left({\psi _{n}^{*}}^{(o)}+\lambda {\psi _{n}^{*}}^{(1)}+\lambda ^{2}{\psi _{n}^{*}}^{2}+\cdots \right)\left(\psi _{n}^{(o)}+\lambda \psi _{n}^{(1)}+\lambda ^{2}\psi _{n}^{(2)}+\cdots \right)\end{aligned}}}

Where: {\displaystyle {\begin{aligned}\lambda ^{o}:\ 1&=\int {\psi _{n}^{(o)}}^{*}\psi _{n}^{(o)}\\\lambda ^{1}:\ 0&=\int {\psi _{n}^{(0)}}^{*}\psi _{n}^{(1)}+\int {\psi _{n}^{(1)}}^{*}\psi _{n}^{(o)}\\\lambda ^{3}:\ 0&=\int {\psi _{n}^{(0)}}^{*}\psi _{n}^{(2)}+\int {\psi _{n}^{(1)}}^{*}\psi _{n}^{(1)}+\int {\psi _{n}^{(2)}}^{*}\psi _{n}^{(o)}\end{aligned}}}

Thus:

${\displaystyle 0=\underbrace {\int {\psi _{n}^{(o)}}^{*}\psi _{n}^{(1)}} _{=a_{nn}}+\underbrace {\int {\psi _{n}^{(1)}}^{*}\psi _{n}^{(o)}} _{{=a_{nn{^{(1)}}}}^{*}}}$

which is a projection of ${\displaystyle \psi _{n}^{(1)}}$ onto ${\displaystyle \psi _{n}^{(o)}}$.

${\displaystyle a_{nn}^{(1)}+{a_{nn}^{(1)}}^{*}=0}$ is a complex number.

Complex number formula: {\displaystyle {\begin{aligned}0&=a+bi+a-bi\\0&=a\end{aligned}}}

What is ${\displaystyle b}$? Here, we choose ${\displaystyle b=0}$.

<FIGURE> "Title" (Description)

In quantum mechanics usually, but not always, ${\displaystyle \Psi }$ can have arbitrary phase ${\displaystyle \phi }$, so long as magnitude of ${\displaystyle \Psi }$ is correct. Here we choose ${\textstyle \phi =0}$. Therefore:

${\displaystyle a_{nn}^{(1)}=0}$

This dictates that all of ${\displaystyle \psi _{n}^{(1)}}$ is orthogonal to ${\displaystyle \psi _{n}^{(o)}}$.

As an example, consider adding a correction to the hydrogen atom, what is actually a fairly common occurrence.

{\displaystyle {\begin{aligned}H&=H_{o}+H'\\H_{o}&={-\hbar ^{2} \over 2m}\Delta ^{2}-{e^{2} \over r}\\H'&=-G{mM_{p} \over r}\end{aligned}}}

This last equation is the influence of gravitational attraction between the positive ion and the negative ion. This is a first order energy correction.

{\displaystyle {\begin{aligned}E_{1s}^{(1)}&=\int {\psi _{1s}^{(o)}}^{*}\left({-GmM_{p} \over r}\right)\psi _{1s}^{(o)}\operatorname {d} \!right\\\psi _{1s}^{(o)}&={1 \over {\sqrt {\pi }}}{1 \over a_{o}^{3 \over 2}}\exp \left[{-2r \over a_{o}}\right]{-GmM \over r}\\\\E_{1s}^{(1)}&=\int _{0}^{\pi }\sin \!\theta \operatorname {d} \!\theta \int _{0}^{2\pi }\operatorname {d} \!\phi \int _{0}^{\infty }r^{2}\operatorname {d} \!r{1 \over \pi }{1 \over a_{o}}\exp \left[{-2r \over a_{o}}\right]{-GmM \over a_{o}^{2}}\left({a_{o}^{2} \over 4}\right)\\&=4\pi {-GmM \over \pi a_{o}^{3}}\int _{0}^{\infty }\operatorname {d} \!rr\exp \left[{-2r \over a_{o}}\right]\\&=-4{GmM \over a_{o}^{3}}\left({a_{o}^{2} \over 4}\right)\end{aligned}}}

When working with degenerate wavefunctions, the problem becomes slightly more complicated because the interactions amongst the degenerate wavefunctions must be carefully accounted for. That said, this is just bookkeeping. The general procedure for Rayleigh-Schrodinger perturbation theory is as outlined here.

 Electronic Properties of Materials/Quantum Mechanics for Engineers ← Quantum Mechanics for Engineers/Variational Methods Perturbation Methods Quantum Mechanics for Engineers/Many Electron Atoms →